Diversity Profiling of Grapevine Microbial Endosphere and Antagonistic Potential of Endophytic Pseudomonas Against Grapevine Trunk Diseases - Niem, Jennifer Millera; Billones-Baaijens, Regina; Stodart, Benjamin; Savocchia, Sandra (Frontiers in Microbiology, 2020)
Grapevine trunk diseases (GTDs) are a serious problem of grapevines worldwide. The microbiota of the grapevine endosphere comprises prokaryotic and eukaryotic endophytes, which may form varied relationships with the host plant from symbiotic to pathogenic. To explore the interaction between grapevine endophytic bacteria and GTDs, the endomicrobiome associated with grapevine wood was characterized using next-generation Illumina sequencing. Wood samples were collected from grapevine trunks with and without external symptoms of GTD (cankers) from two vineyards in the Hunter Valley and Hilltops, NSW, Australia and metagenomic characterization of the endophytic community was conducted using the 16S rDNA (341F/806R) and ITS (1F/2R) sequences. Among the important GTD pathogens, Phaeomoniella, Phaeoacremonium, Diplodia and Cryptovalsa species were found to be abundant in both symptomatic and asymptomatic grapevines from both vineyards. Eutypa lata and Neofusicoccum parvum, two important GTD pathogens, were detected in low numbers in Hilltops and the Hunter Valley, respectively. Interestingly, Pseudomonas dominated the bacterial community in canker-free grapevine tissues in both locations, comprising 56-74% of the total bacterial population. In contrast, the Pseudomonas population in grapevines with cankers was significantly lower, representing 29% and 2% of the bacterial community in Hilltops and the Hunter Valley, respectively. The presence of Pseudomonas in healthy grapevine tissues indicates its ability to colonize and survive in the grapevine. The potential of Pseudomonas spp. as biocontrol agents against GTD pathogens was also explored. Dual culture tests with isolated fluorescent Pseudomonas against mycelial discs of nine Botryosphaeria dieback, three Eutypa dieback, and two Esca/Petri disease pathogens, revealed antagonistic activity for 10 Pseudomonas strains. These results suggest the potential of Pseudomonas species from grapevine wood to be used as biocontrol agents to manage certain GTD pathogens.